Antibacterial activities of the extracts of sponge Agelas cervicornis agains bacteria Staphylococcus aureus - Denatri, Ardelia Humaimah; Maisaroh, Dian Sari; Kartika, Ary Giri Dwi; Susanti, Oktora; Munir, Misbakhul (Journal of Marine Resources and Coastal Management, 2023)
Infection is a health problem that can cause death in the world. An antibiotics is a treatment used to treat infectious diseases. If antibiotics are used continuously, they can cause resistance. One of the bacteria that causes skin infections and has been reported to be resistant to several antibacterials is Staphylococcus aureus. So we need an alternative to exploring antibacterial compounds derived from the ocean. Sponge extract from the genus Agelas has been reported to contain secondary metabolites that are antibacterial. This research aims to determine the antibacterial potential of sponge extract and the secondary metabolite of sponge extract, Agelas cervicornis. The extraction process uses maceration with methanol as a solvent. The tests carried out in this study included a phytochemical screening test and an antibacterial activity test carried out using the disc diffusion method to determine the inhibition zone produced against the pathogenic bacteria Staphylococcus aureus. The results of phytochemical screening showed that the sponge extract of Agelas cervicornis contained flavonoids, alkaloids, and terpenoids. The results of the antibacterial activity test of the sponge extract of Agelas cervicornis showed that all concentrations of 0.5 mg/ml, 1 mg/ml, and 1.5 mg/ml had weak inhibitory properties.